PENGARUH KUALITAS INFORMASI, KEMUDAHAN, DAN KEPERCAYAN TERHADAP KEPUTUSAN PEMBELIAN DI SITUS TOKOPEDIA - Irmawati Irmawati; Mursyid Risma Nofi Cahyanto (House of Management and Business (HOMBIS) Journal, 2022)
This research aims to analyze the influence of information quality, ease, and belief on the decision of purchasing online in the Surakarta community of Tokopedia site users. The samples used in this study were 100 respondents (Tokopedia users) in Surakarta using the questionnaire to make up the data. The sampling technique is Purposive sampling which is a sampling method where the researcher determines the sampling by defining specific characteristics such as TOKOPEDIA site users because the number of the population is scattered and difficult to know for sure. Data analysis techniques using validity and reliability tests, classical assumption tests using normality testing, multicollinearity tests, heteroskedasticity tests, multiple linear regression tests, hypothesis tests using t-tests, F tests, and coefficient of determination tests. The results of this study showed that the variable quality, is significantly influential to the purchase decision online, the variable of ease of influence significantly towards the purchase decision, and the variable Hu significantly influence the decision the purchase online.